2014
DOI: 10.1002/ajp.22310
|View full text |Cite
|
Sign up to set email alerts
|

Which is the appropriate scale to assess the impact of landscape spatial configuration on the diet and behavior of spider monkeys?

Abstract: Understanding the response of species to changes in landscape configuration is required to design adequate management and conservation strategies. Yet, the most appropriate spatial scale (i.e., landscape size) to assess the response of species to changes in landscape configuration (so-called "scale of effect") is largely unknown. In this paper, we assess the impact of landscape forest cover, forest fragmentation, edge density, and inter-patch isolation distance on the diet and behavior of six communities of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
2
25
0
2
Order By: Relevance
“…Forest configuration can also be measured at the patch (e.g., patch shape and isolation) and landscape scales (e.g., degree of fragmentation; Cushman et al 2008;McGarigal et al 2012). It is unclear, however, which is the scale within which forest loss and configuration has the strongest effect on biodiversity (but see Smith et al 2011;Thornton et al 2011;Arroyo-Rodríguez et al 2013;Fahrig 2013;Ordóñez-Gómez et al 2015). To address this challenge, multiscale analyses are needed.…”
Section: Introductionmentioning
confidence: 97%
“…Forest configuration can also be measured at the patch (e.g., patch shape and isolation) and landscape scales (e.g., degree of fragmentation; Cushman et al 2008;McGarigal et al 2012). It is unclear, however, which is the scale within which forest loss and configuration has the strongest effect on biodiversity (but see Smith et al 2011;Thornton et al 2011;Arroyo-Rodríguez et al 2013;Fahrig 2013;Ordóñez-Gómez et al 2015). To address this challenge, multiscale analyses are needed.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, a combination of site‐ and landscape‐level variables seems to drive primate populations (Boyle et al, ; Carretero‐Pinzón, Defler, McAlpine, & Rhodes, ). However, primate studies generally measure landscape variables at a single spatial scale (Anzures‐Dadda & Manson, ; Benchimol & Peres, ; Benchimol & Venticinque, ; Silva, Ribeiro, Hasui, Costa, & da Cunha, ), and when considering multiple scales, they select scales with a small range of variation (landscape sizes <7 km 2 ; Arroyo‐Rodríguez et al, ; Galán‐Acedo et al, ; Ordóñez‐Gómez, Arroyo‐Rodríguez, Nicasio‐Arzeta, & Cristóbal‐Azkarate, ) and/or just a few different spatial scales (Arroyo‐Rodríguez, Cuesta‐del Moral, et al, ; Carretero‐Pinzón et al, ; Thornton et al, ). These methodological issues may prevent the identification of accurate scales of effect (Jackson & Fahrig, )—a critical step for improving primate conservation and restoration planning.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in Tanzania, forest sites surrounded by higher forest cover can show more individuals of Pan troglodytes (Piel et al, ), and a higher number of primate species (Blanco & Waltert, ). Ordóñez‐Gómez et al () also demonstrate that Geoffroyi's spider monkeys ( Ateles geoffroyi ) spent more time travelling and feeding in landscapes with more forest cover (Fig. B).…”
Section: Resultsmentioning
confidence: 84%
“…Those studies that assessed the scale of effect reported scales ranging from 0.39‐km (Ordóñez‐Gómez et al, ) to 5.5‐km radius (Rabelo et al, ). The cause of such differences remains poorly understood, but following previous studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation